A comparative analysis of experimental and numerical investigations of composite tubes under axial and lateral loading - Aljibori H.S.S.; Al-Qrimli H.F.; Ramli R.; Mahdi E.; Tarlochan F.; Chong W.P. (2023)
Quasi-static tests are performed in order to determine the crash behavior of composite tubes. The specimens are made from woven fiber carbon/epoxy. The crash experiments show that the tubes crushed in a progressive manner from one end to the other of the tubes while delamination was - taking place between the layers. In the simulation works described in this paper the ANSYS explicit finite element code is used to investigate the compressive properties and crushing response of circular carbon tube subjected to static axial and lateral loading and the results are compared with the experimental work. To better understand the details of the crash process, thin multi layer shell elements are used to model the walls of the circular tube. Finally, the design optimization technique is implemented to find an optimum composite configuration that has the maximum failure load and absorbs the most energy. The crash performance of a carbon composite shell is compared with an optimum carbon tube from the experimental work. 2010, INSInet Publication.